2013
DOI: 10.1111/jir.12096
|View full text |Cite
|
Sign up to set email alerts
|

Exercise reduced inflammation: but for how long after training?

Abstract: A 3-month detraining period significantly impaired chronic inflammation in obese women with DS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(54 citation statements)
references
References 29 publications
1
23
0
2
Order By: Relevance
“…Similar results were found in previous studies that focused on RT intervention programs [32,33] or mixed protocols that combined both RT and endurance training [34]. Previous studies based on endurance training [35] or whole-body vibration training [36] have also reported promising results.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were found in previous studies that focused on RT intervention programs [32,33] or mixed protocols that combined both RT and endurance training [34]. Previous studies based on endurance training [35] or whole-body vibration training [36] have also reported promising results.…”
Section: Discussionsupporting
confidence: 88%
“…Of the total, 17 trials reported comparable baseline and post-intervention data for both the intervention and control groups and were included in the meta-analysis. From these, three publications were derived from the same sample (Ordoñez et al 2013;Ordonez et al 2014;Rosety-Rodriguez et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…A total of eight trials informed about the ID level of the sample, identified through specific scales (Stanford-Binet Scale and Wechsler Scale) as mild (Ordoñez et al 2013;Ordonez et al 2014;Rosety-Rodriguez et al 2014;Melville et al 2015), moderate (Lin & Wuang 2012;Melville et al 2015;Mikolajczyk & Jankowicz-Szymanska 2015), mild to moderate (Ozmen et al 2007;Shields & Taylor 2015) and severe (Melville et al 2015). When ID level was not reported, ID condition was determined through medical diagnosis (i.e.…”
Section: Design and Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated ratio measures provide further evidence that each form of exercise presents a markedly different stress stimulus (Figure 1). Moreover, only the RSA test caused CRP corrected for plasma volume loss level to increase, while TP and albumin changes were related with post-effort dehydration before a return to baseline values during recovery (Table 3) [50,51]. On the other hand, the lack of a significant decrease in C2 and C4 protein level following the Beep test lends support to an alternative pathway of complement activation [8].…”
Section: Discussionmentioning
confidence: 97%